Przymierza Izraelitów z narodami w świetle zakazów Pięcioksięgu Biblii greckiej - Nawrot, Janusz (Poznańskie Studia Teologiczne, 2021)
The conducted exegesis of some particular verses from the Septuagint indicates that two initial covenants made between a representative of the chosen nation with a Gentile party (Abraham and Solomon) did not breach the obligations resulting from the Law of Moses. The theological portrait of Abraham in the Book of Genesis captures an unambiguous evaluation of his conduct in accordance with the Law although the Law itself appeared considerably later when Moses lived. The pact between Solomon and Hiram deserves a similar evaluation. However, the later covenants between the kings of Israel and Judah with Gentile rulers deserve an extremely negative evaluation. Although they did not formally violate the Mosaic prohibitions, they were evaluated as a violation of trust in the Lord as He was the only Partner of the covenant between Himself and the Israelites. Such an interpretation is possible especially in light of Deut 7:6 which accentuates the uniqueness of Israel as a nation chosen by God from among other nations. And because this selection of Israel was done on the foundation of the covenant made on the Mount Sinai, it should be a one-of-a-kind covenant that should not be replaced with another pact signed with a human being, and let alone a Gentile. In all of the cases above, starting from King Asa and ending with Archpriest Jonathan, there was a true violation of the rule whereby the Lord was the only Partner of the covenant with His people. Thus, each of the analyzed treatises met with valid criticism both from a prophet and the inspired author. It is difficult to treat these violations as a major breach of the faith of Israel because of the established diplomatic relations. However, it was the rule of God’s uniqueness as a foundation for any sphere in the life of the chosen people that was violated. It included the political sphere which should not be excluded from the chosen people’s faith.